If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(x+6)+5=14
We move all terms to the left:
9(x+6)+5-(14)=0
We add all the numbers together, and all the variables
9(x+6)-9=0
We multiply parentheses
9x+54-9=0
We add all the numbers together, and all the variables
9x+45=0
We move all terms containing x to the left, all other terms to the right
9x=-45
x=-45/9
x=-5
| 6×5(m+1)=26 | | 85=v-539 | | 8(x-9)-9=-65 | | -3y-10=2y+20 | | -11+k=-8-3(k-)11 | | 4(x+13)-8=48 | | 8x+4(x-3=4(6x+4)-4 | | 28y=532 | | 4(x+14)=64 | | z/12=20 | | 2x-13=7-3x | | a²-22a+121=0 | | 3x-4*4=65 | | H=16(t-3)^2+189 | | 8(x+9)-18=-162 | | 2^1-3x=99 | | 5x+4-2x-3=0 | | 5(x+6)+12=-3 | | 2(x+10)=14 | | 5(x+13)=65 | | 7(x+5)-9=-23 | | 3x-41/2=-19 | | 7(x+17)+11=137 | | 1.5(1+3r)=2/3(2-3r) | | 92=4g | | 37-8x=157 | | 5(x+8)-19=-19 | | 2m=4m-2 | | 10(x+13)+14=144 | | 6(x+9)-12=66 | | 75y-5=-1+.25y | | 7(x+14)+19=54 |